2007
DOI: 10.1007/s12011-007-8043-1
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Osteoporotic Changes of Mineral Composition in Femurs of Diabetic Rats by Insulin

Abstract: Insulin plays an important role in bone prevention of diabetic osteoporosis, but little is known about the relation between the bone mineral density (BMD) increase and the change of mineral element content after treated with insulin. To address this problem, male Wistar rats were randomly divided into three groups: normal group (n = 6), streptozotocin-induced diabetic group (n = 5), and streptozotocin-induced diabetic group with insulin treatment (n = 5). The femoral BMD was measured by dual energy X-ray absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Studies have shown that trace elements play an important part in the maintenance of BMD, acting directly on the deposition of Ca, P and Mg [29]. In our model, the femur was divided equally into six ROI (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that trace elements play an important part in the maintenance of BMD, acting directly on the deposition of Ca, P and Mg [29]. In our model, the femur was divided equally into six ROI (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In early rat studies, daily subcutaneous injections of insulin improved the structural strength of the femur mid-shaft (Dixit and Ekstrom, 1980) and femoral neck (Hou et al, 1993) when compared to untreated alloxan-induced T1D rats. Recent rat studies report daily subcutaneous injections of insulin nearly restored the STZ-related loss i) in peak force endured by the femur mid-shaft during three-point (3 pt) bending (Rao Sirasanagandla et al, 2014), ii) in total femur aBMD (Zhang et al, 2008), iii) in femoral neck and mid-shaft diameters (Abd El Aziz et al, 2015), iv) in femur mid-shaft aBMD (but not in tensile mechanical properties) (Erdal et al, 2012), and v) in peak bending stress (but not in peak force during 3 pt. bending) of the tibia mid-shaft (Bortolin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that diabetic bones present lower mainly because of dysfunction in bone cell formation, leading to a lower bone mechanical strength (27). Furthermore, higher values of fracture force were observed in both trained groups and higher values of stiffness were observed in TLG.…”
Section: Discussionmentioning
confidence: 87%
“…Zhang and cols. (27) have demonstrated a decreased femoral BMD in diabetic animals compared to normal animals. Additionally, Mathey and cols.…”
Section: Discussionmentioning
confidence: 93%